KIR2DS4 and its variant KIR1D in KIR-AA genotype donors showed differential survival impact in patients with lymphoid disease after HLA-matched unrelated hematopoietic stem cell transplantation - Gowdavally, Sowmya; Tsamadou, Chrysanthi; Platzbecker, Uwe; Sala, Elisa; Valerius, Thomas; Klein, Stefan; Kröger, Nicolaus; Wulf, Gerald; Einsele, Hermann; Thurner, Lorenz; Schaefer-Eckart, Kerstin; Freitag, Sebastian; et al. (Transplantation and cellular therapy, 2023)
Previous studies have illustrated associations between the presence of activating killer cell immunoglobulin-like receptor (KIR) genes and lower susceptibility to hematologic malignancies in humans. In addition, favorable hematopoietic stem cell transplantation (HSCT) outcomes have been reported in patients who received transplants from donors with KIR genotypes dominant for activating KIR receptors. However, the association of activating KIR genes on an allelic level with disease and their impact on HSCT outcome has been little investigated to date. To this end, we genotyped a large transplantation cohort for KIR 2 Ig domains and short cytoplasmic tail 4 (KIR2DS4) polymorphisms and investigated their association with disease. We next investigated the impact of KIR-AA genotype donor KIR2DS4 polymorphisms (AA/KIR2DS4 versus AA/ KIR 1 Ig domain [KIR1D]) on clinical outcomes of HSCT in myeloid versus lymphoid patient subgroups. Among 2810 transplantation donor-recipient pairs, 68.8% (n = 1934) were 10/10 HLA-matched and 31.2% (n = 876) were 9/10 HLA-matched. The distribution of KIR1D was equal in patients and donors (P = .205). Multivariate analysis in 10/10 HLA-matched patients with lymphoid disease showed improved HSCT outcomes when they received grafts from AA/KIR1D donors (overall survival: hazard ratio [HR], .62, P = .002; disease free survival: HR, .70, P = .011; graft-versus-host disease-free and relapse-free survival: HR, .67, P = .002; nonrelapse mortality: HR, .55, P < .001). This effect was not seen in either 9/10 HLA-matched patients with lymphoid disease or patients with myeloid disease. Our study indicates that the presence of KIR1D alleles is not associated with disease in patients, and, interestingly, using grafts from AA/KIR1D donors translated into beneficial survival outcomes in 10/10 HLA-matched patients with lymphoid disease.